Identification of the Gene Repertoire of the IMD Pathway and Expression of Antimicrobial Peptide Genes in Several Tissues and Hemolymph of the Cockroach Blattella germanica - Zuber, Leo; Domínguez-Santos, Rebeca; García-Ferris, Carlos; Silva, Francisco J. (International journal of molecular sciences, 2022)
Antimicrobial peptide (AMP) genes, triggered by Toll and IMD pathways, are essential components of the innate immune system in the German cockroach Blattella germanica. Besides their role in killing pathogenic bacteria, AMPs could be involved in controlling its symbiotic systems (endosymbiont and microbiota). We found that the IMD pathway was active in the adult female transcriptomes of six tissues (salivary glands, foregut, midgut, hindgut, Malpighian tubules and fat body) and hemolymph. Total expression of AMP genes was high in hemolymph and salivary glands and much lower in the other sample types. The expression of specific AMP genes was very heterogeneous among sample types. Two genes, defensin_g10 and drosomycin_g5, displayed relevant expression in the seven sample types, although higher in hemolymph. Other genes only displayed high expression in one tissue. Almost no expression of attacin-like and blattellicin genes was observed in any sample type, although some of them were among the genes with the highest expression in adult female whole bodies. The expression of AMP genes in salivary glands could help control pathogens ingested with food and even determine gut microbiota composition. The low expression levels in midgut and hindgut are probably related to the presence of beneficial microbiota. Furthermore, a reduction in the expression of AMP genes in fat body could be the way to prevent damage to the population of the endosymbiont Blattabacterium cuenoti within bacteriocytes.